Reconsidering Kant’s Copernican Revolution: From Synthetic A Priori Knowledge to the Metaphysical Status of the Noumenon - Öztürk, Burak (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This paper critically examines Michael J. Olson’s interpretation of Kant’s Copernican Revolution as a transformation of the object of metaphysics into synthetic a priori knowledge with a twofold structure. While granting Olson’s insight that the Copernican Revolution is not merely a perspectival reversal but a substantive reconfiguration of metaphysics modeled on the methodological revolutions in mathematics and physics, I argue that his account remains incomplete. In particular, Olson’s interpretation risks reducing Kant’s critical project to an epistemological enterprise. By focusing on Kant’s phenomenon–noumenon distinction, I show that transcendental idealism involves unavoidable metaphysical commitments that cannot be captured solely in terms of synthetic a priori knowledge. Although noumena are not objects of knowledge, they function as necessary limiting concepts and as the metaphysical ground of appearances. Consequently, Kant’s Copernican Revolution should be understood as a rearticulation rather than a replacement of metaphysics.